Biochemical and toxicological evaluation of Solanum viarum fruit extract on Dugesia tigrina - Schaly, Felipe; Braguini, Welligton Luciano (Archives of Biological Sciences, 2024)
Paper description: The environmental risk of Solanum viarum fruit extract on planarians was examined because of its toxicity to livestock. Dugesia tigrina served to evaluate locomotor velocity, reproduction, glycogen content, antioxidant enzyme and acetylcholinesterase activities; phytochemical analysis and toxicity assays were performed. AEF from viarum reduced planarian locomotion, fecundity, fertility, glycogen content, and affected enzymes. This study highlights the need for environmental risk assessments and future research on natural compounds extracted from viarum. Abstract: Solanum viarum has alkaloid-rich fruits. We evaluated the antioxidant and chelating activities of the aqueous extract fraction (AEF) from S. viarum fruits and its effects on the brown planarian Dugesia tigrina. The AEF demonstrated an iron-chelating effect comparable to ascorbic acid but lower than EDTA and a significant reducing power. The 96-h LC50 for planarians was 1.22 g/L. At a concentration of 0.50 g/L, the AEF reduced planarian locomotor velocity by 34.7%, while decreasing fecundity and fertility by 98.4% and 96.7%, respectively, leading to a significant decline in the number of cocoons and emerging planarians. Cocoon hatching time was increased at all AEF concentrations. Planarians exposed to 0.50 g/L AEF for 14 days showed a 62.3% reduction in glycogen content. After 14 days, catalase was inhibited at all concentrations, with 83.2% inhibition at 0.50 g/L. Superoxide dismutase (SOD) increased by 60.8% and 59.9% after 24 h and 14 days, respectively, at 0.50 g/L AEF. Catalase (CAT) was stimulated by 72.1% and 44% at 0.10 and 0.25 g/L AEF, respectively, but inhibited by 25.2% at 0.50 g/L after 24 h. The iron-chelating activity of the AEF reduces iron availability for catalase, an iron-dependent enzyme, leading to its inhibition, while also limiting Fenton and Haber-Weiss reactions, resulting in hydrogen peroxide accumulation and subsequent stimulation of SOD under prolonged exposure. Acetylcholinesterase (AChE) was stimulated by 40.6% and 44.8% after 24 h and 14 days, respectively, at 0.50 g/L AEF. These findings show that S. viarum is harmful to planarians and may pose environmental risks, highlighting the need for toxicity assessments in other species.